Quality of life in patients with Tuberous Sclerosis Complex (TSC). (November 2019) - Amin, Sam; Mallick, Andrew A.; Lux, Andrew; O'Callaghan, Finbar
Abstract: Background: The quality of life (QoL) of patients with Tuberous Sclerosis Complex (TSC) has not been studied before. We aimed to investigate the impact of the disease on QoL. We studied the QoL of 91 TSC patients who have attended the Bath TSC clinic, UK over 6 months. QoL was evaluated using the PedsQL for children, and SF-36 for adults. Results: Impaired QoL is found in all patients with TSC regardless of the presence of epilepsy and learning disabilities (LD). Total mean self-reported score for children was 71 out of 100, compared to a UK norm of 84, p < 0.000. The proxy mean score was 48, (UK norm 85, p < 0.000). Physical Functioning score for adults with TSC was 70, compared to a UK norm of 94, p < 0.000. The Social Functioning score for adults with TSC was 71, (UK norm 88, p < 0.000). Conclusions: Impaired QoL is found in all patients with TSC regardless of the presence of epilepsy and learning disabilities. The psychosocial domain is most affected. The quality of life of children with TSC is lower than children who suffer from asthma, diabetes, cancer and inflammatory bowel disease. To improve health related quality of life in TSC, a focus on patient's physical health, educational performances, and overall quality of life is crucial. In order to achieve this, coordinated medical care across disciplines, and psychosocial and social support is necessary. Highlights: Impaired QoL is found in all patients with TSC regardless of the presence of epilepsy and LD. The psychosocial domain is most affected. The QoL of children with TSC is lower than children who suffer from asthma, diabetes, cancer and inflammatory bowel disease.